2021
DOI: 10.3168/jds.2020-18811
|View full text |Cite
|
Sign up to set email alerts
|

Invited review: Microfiltration-derived casein and whey proteins from milk

Abstract: Milk, a rich source of nutrients, can be fractionated into a wide range of components for use in foods and beverages. With advancements in filtration technologies, micellar caseins and milk-derived whey proteins are now produced from skim milk using microfiltration. Microfiltered ingredients offer unique functional and nutritional benefits that can be exploited in new product development. Microfiltration offers promise in cheesemaking, where microfiltered milk can be used for protein standardization to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
76
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 96 publications
(77 citation statements)
references
References 93 publications
1
76
0
Order By: Relevance
“…The separation is determined by the membrane characteristics (molecular weight cutoff value) and the molecular size of the individual components present in the feed. Two of the major separation technologies employed in the dairy industry are ultrafiltration (UF), and microfiltration (MF) [1]. These two processes differ in membrane characteristics, pore size and operating pressure.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The separation is determined by the membrane characteristics (molecular weight cutoff value) and the molecular size of the individual components present in the feed. Two of the major separation technologies employed in the dairy industry are ultrafiltration (UF), and microfiltration (MF) [1]. These two processes differ in membrane characteristics, pore size and operating pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Dairy 2021, 2, 367-384. https://doi.org/10.3390/dairy2030029 https://www.mdpi.com/journal/dairy UF is primarily used to produce dairy ingredients that have an increased protein content and reduced lactose contents, such as milk protein concentrate (MPC) and whey protein concentrate (WPC). Since the typical UF membrane has a pore size of approximately 10 kD, it retains the fat, CN, SP and colloidal minerals, whereas particles below 10 kD in size-such as lactose and soluble minerals-pass through the membrane into the permeate [1][2][3]. A major application of UF processing is the production of MPC varying in protein content from 50% to 85%.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three different whey/serum protein isolates (WPI/SPI) were sourced in duplicate lots from different processing methods (ion exchange, microfiltration of cheese whey, and direct microfiltration of skim milk). SPI is also called milk soluble whey protein and refers to whey protein isolated directly from milk rather than from fluid whey (Carter, Cheng, Kapoor, Meletharayil, & Drake, 2021). Actual protein content of liquid or powdered proteins were confirmed by an infrared spectrophotometer (Lactoscope FTIR, Delta Instruments, Drachten, the Netherlands).…”
Section: Methodsmentioning
confidence: 99%
“…Compared to these systems, membrane separation systems using polymeric membranes have a smaller footprint, are inexpensive, and are familiar to most of the US dairy processors. In recent years, the interest in assessing the suitability and efficiency of polymeric MF membranes for MCC production has been increased [5,7,21,[23][24][25][26][27]. It has been shown that using ceramic membranes, over 95% of serum protein could be removed in a three-stage process in which diafiltration (DF) to a level of 200% (on the basis of feed volume) was used.…”
Section: Introductionmentioning
confidence: 99%